Upaya Meringankan Biaya Penerangan Gerobak Kaki Lima Di Saat Pandemi COVID-19 Dengan LED Bertenaga Surya - Mauludi Manfaluthy (Sekolah Tinggi Teknik - PLN, 2021)
One of the impacts of the COVID 19 pandemic is that the purchasing power of each person has become weak, the economic burden which is quite pressing on the entire community is felt more by food cart traders. Sales hours are also limited, on the other hand, operations must be kept running. Entering the month of Ramadan, the hours of selling are more in the afternoon before breaking the fast until late at night, street cart traders need lighting lights. This is an additional burden that must be borne without being able to compensate for the selling price. We have done community service; we conducted socialization on the use of LED Lighting which can get a source from solar cells and can be charged like a cellphone. From our observations, it can help traders reduce the burden of electricity costs.